2011
DOI: 10.1111/j.1532-950x.2011.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Computed Tomographic and Radiographic Popliteal Lymphangiography in Normal Dogs

Abstract: CT popliteal lymphangiography consistently identified a greater number of TD branches when compared with radiographic popliteal lymphangiography. Injection of either popliteal lymph node resulted in the same number of TD branches being observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Several lymphangiographic studies have investigated the use of CT to assess the thoracic duct and its tributaries in dogs . However, to the authors’ knowledge, no published studies have described the specific appearance of the cisterna chyli using CT.…”
Section: Introductionmentioning
confidence: 99%
“…Several lymphangiographic studies have investigated the use of CT to assess the thoracic duct and its tributaries in dogs . However, to the authors’ knowledge, no published studies have described the specific appearance of the cisterna chyli using CT.…”
Section: Introductionmentioning
confidence: 99%
“…However, as Singh et al (2010) did not find a significant difference in the number of observed lymphatic branches after left or right intrapopliteal iohexol injection during a radiographic and CT scan study in the dog, we hypothesised that the injection side should not have any impact on the results.…”
Section: Discussionmentioning
confidence: 94%
“…The image diagnostic tools used were computed tomography (CT), tomography lymphangiography and echocardiogram. The CT made it possible to identify the thoracic organs, as well as the thoracic duct and its ruptured spots, because this equipment gives a tridimensional image with good resolution, lowering the interference of adjacent tissues overlap [12,13].…”
Section: Discussionmentioning
confidence: 99%